Prevalence of non-alcoholic fatty liver disease among the working-age population: associations with socio-demographic indicators and behavioral risk factors (ESSE RF-2 data) - S. E. Evstifeeva; S. A. Shalnova; V. A. Kutsenko; E. V. Yarovaya; Yu. A. Balanova; A. E. Imaeva; A. V. Kapustina; G. A. Muromtseva; S. A. Maksimov; N. S. Karamnova; A. G. Soplenkova; E. M. Filichkina; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To assess the prevalence of non-alcoholic fatty liver disease (NAFLD) using the liver obesity index — FLI (Fatty Liver Index), and to study its associations with socio-demographic indicators and behavioral risk factors for NAFLD.Material and methods. The data from the multicenter ESSE-RF study (Epidemiology of cardiovascular diseases in the regions of the Russian Federation) — samples from the unorganized male and female population aged 25-64 years were used. 5,161 respondents were included, of which 2,275 (44,1%) were men. To assess the prevalence of NAFLD, the liver obesity index FLI was used, calculated according to the formula by Bedogni G, et al. (2006). A high FLI index ≥60 was considered a predictor of liver steatosis.Results. High FLI ≥60 was detected in 38,5% of men and 26,6% of women. Multivariate analysis of associations of high FLI index in men and women showed a strong relationship with age: men — odds ratio (OR) 5,01, 95% confidence interval (CI): 3,82-6,59 (p<0,0001) and women — OR 8,58, 95% CI: 6,39-11,64 (p<0,0001), living in rural areas: men — OR 1,32, 95% CI: 1,06-1,63 (p=0,011) and women — OR 1,4, 95% CI: 1,15-1,71 (p=0,001). The FLI index ≥60 was significantly associated with low physical activity (p=0,001) in men and current smoking in women (p=0,013).Conclusion. A high FLI index ≥60 is most common among men, significantly associated with age, living in rural areas, currently smoking women, and low physical activity men. Higher education, in relation to FLI ≥60, had a protective effect on women.